Kualitas Layanan Elektronik: Sebuah Gagasan Model Awal - Noor, Irwan (Jurnal Ilmiah Administrasi Publik, 2019)
The delivery of quality public services is the main function of the public sector. The span of administrative science is generally concerned with achieving quality public services. However, different viewpoints in understanding public services can provide the wrong point of view. Generally, the point of view is viewed from two different angles. First, the service provider (government). Second, from the recipient of the service (stakeholders). This paper provides a new nuance in a model, which is seeing the quality of service from both sides. The model we called "Initial Model Ideas".